The relationship between job stress, job performance and job motivation among police officers at the federal territory police headquarters - Arujunan, Kalaikumar; Ismail, Ismi Arif; Othman, Shamsuddin; Arshad, Mohd Mursyid (Macrothink Institute, 2021)
Job performance is an important aspect of employees which ensures the efficiency and effectiveness of an organization. Job performance is influenced by job stress, while job stress affects job motivation. Hence, this paper is intended to identify the relationship between these three variables among Royal Malaysia Police (PDRM) officers at the Federal Territory Police Headquarters. This is a quantitative study for which data has been collected from 341 police officers through a survey. Data was analyzed statistically using PLS-SEM. Findings showed that there was a significant, negative relationship between job performance and job stress; and between job stress and job motivation.